Response of NPK Fertilizer on the Incidence of Pod Borer, Helicoverpa Armigera (Hubner) and Grain Yield of Chickpea (Bangladesh Journal of Scientific and Industrial Research, 2009)
Different dose of NPK fertilizer had shown both negative and positive influence on pod borer damage. In general, application of low to moderate doses of NPK reduced pod borer damage. Application of higher doses NPK increased pod borer damage compared to untreated control. Pod borer damage reduction by low to moderate doses of NPK fertilizer application ranged from 3.10 to 14.22%. The highest pod damage reduction (14.22%) was found in 20-20-20 kg NPK/ha followed by 40-20-20 kg NPK/ha (14.00%) and 20-40-20 kg NPK/ha (12.42%). While, pod borer damage was increased by higher dose levels of NPK fertilizer application which ranged from 4.34 to 15.81 %. Manuring with NPK fertilizer in chickpea increased grain yield upto 34.62%. The highest yield (1750kg/ha) was obtained from 20- 40-20 kg NPK/ha, which was statistically identical among levels of NPK application except 20-20-20 kg NPK/ha. The lowest yield (1300kg/ha) was recorded from control treatment. The highest marginal benefit cost ratio (4.35) computed from the manurial combination 40-20-20 kg NPK/ha followed by 20- 40-20 kg NPK/ha (MBCR 3.73) Manurial combination 40-20-20 kg NPK/ha was found most profitable followed by 20-40-20 kg NPK/ha in considering pod borer damage and yield in chickpea cultivation. Key words : Chickpea, Pod borer, NPK Fertilizer and Yield   doi: 10.3329/bjsir.v44i1.2720 Bangladesh J. Sci. Ind. Res. 44(1), 117-124, 2009